The Antigen Presenting Cells Instruct Plasma Cell Differentiation - Xu, Wei; Banchereau, Jacques (Frontiers in Immunology, 2014)
The professional antigen presenting cells (APCs), including many subsets of dendritic cells and macrophages, not only mediate prompt but nonspecific response against microbes, but also bridge the antigen-specific adaptive immune response through antigen presentation. In the latter, typically activated B cells acquire cognate signals from T helper cells in the germinal center of lymphoid follicles to differentiate into plasma cells, which generate protective antibodies. Recent advances have revealed that many APC subsets provide not only “signal 1” (the antigen), but also “signal 2” to directly instruct the differentiation process of plasma cells in a T cell-independent manner. Herein, the different signals provided by these APC subsets to direct B cell proliferation, survival, class switching and terminal differentiation are discussed. We furthermore propose that the next generation of vaccines for boosting antibody response could be designed by targeting APCs.